UKURAN PERUSAHAAN, WINNER/LOSER STOCK, DEBT TO EQUITY RATIO, DIVIDEND PAYOUT RATIO PENGARUH TERHADAP PERATAAN LABA - Asri Warnanti, Sri Supriastuti (Paradigma, 2015)
Income smoothing is an effort in controlling earnings management to increase or decrease the companys earnings to reduce fluctuations in earnings. This study aimed to examine the effect of the firm size, winner/loser stock, debt to equity ratio, dividend payout ratio to income smoothing. The population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange (BEI) in the period 2010-2013. The sample was selected using purposive sampling technique and acquired 29 manufacturing companies as sample with 116 observations. The analysis technique used in this study is a multiple regression analysis using SPSS.Results The investigations showed that the firm size and winner/loser stocks have significant influence on income smoothing, while debt to equity ratio and dividend payout ratio does not significantly affect income smoothing.